2008
DOI: 10.1097/ccm.0b013e318170a03b
|View full text |Cite
|
Sign up to set email alerts
|

The impedance cardiogram recorded through two electrocardiogram/defibrillator pads as a determinant of cardiac arrest during experimental studies*

Abstract: As a powerful clinical marker of circulatory collapse, the fast Fourier transformation of dZ/dt (impedance cardiogram) has the potential to improve emergency care by laypersons using automated defibrillators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Studies by Losert et al 18 and Risdal et al 19 concluded that a combination of features extracted from ECG and TI allows a proper discrimination between pulse-generating rhythms (PR) and pulseless electrical activity (PEA). Cromie et al used a single feature computed from the spectrum of the processed TI as a clinical marker of circulatory collapse in animals 20 and humans. 21 In our previous work, we presented a reliable method to extract the impedance circulation component (ICC) using an adaptive processing scheme, and concluded that morphological features extracted from ICC showed great potential for PEA/PR discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Losert et al 18 and Risdal et al 19 concluded that a combination of features extracted from ECG and TI allows a proper discrimination between pulse-generating rhythms (PR) and pulseless electrical activity (PEA). Cromie et al used a single feature computed from the spectrum of the processed TI as a clinical marker of circulatory collapse in animals 20 and humans. 21 In our previous work, we presented a reliable method to extract the impedance circulation component (ICC) using an adaptive processing scheme, and concluded that morphological features extracted from ICC showed great potential for PEA/PR discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for the automated detection of circulation based on the ECG and the TTI signals can be found in the literature [28][29][30][31][32][33][34]. In general, they rely on the analysis of the signals during chest compression pauses, looking for an organized rhythm in the ECG and the circulation component of the TTI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proved that cardiac contractions determine coincident modifications in TTI signal with high sensitivity and specificity [18,19,20], which permit differentiation of PEA from pulse-generating rhythms [20]. On this basis, all stages of CPR in which CodeStat displayed an interruption of chest compressions in the presence of an organized ECG activity were identified and analyzed.…”
Section: Methodsmentioning
confidence: 99%